2004
DOI: 10.1016/j.jneuroim.2003.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation by uptake of fDNA via a scavenger receptor

Abstract: The fate of the fragmented DNA (fDNA) observed in neuronal nuclei in Alzheimer brain is unknown. However, its fate is suggested as fDNA is found in the cytoplasm of adjacent activated microglia. After a brief incubation with fDNA, approximately 70% of microglia had fDNA in their cytoplasm, were activated, and overexpressed interleukin-1β. Microglial activation enhanced uptake whereas blocking scavenger receptors suppressed this uptake. These results suggest that the brain rids itself of fDNA from dying neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…62.5 mcg/mL fucoidan was able to prevent shape change in the LPS exposed microglial cultures, and 125 mcg/mL inhibited NO production. In 2004 Li demonstrated the characteristic fragmented DNA (fDNA) observed in neuronal nuclei in Alzheimer brain was taken up by adjacent activated microglia which then became activated [93]. Blocking the scavenger receptors on the microglial cells with Fucus vesiculosis fucoidan at 40 ng/mL suppressed this uptake.…”
Section: Therapies From Fucoidanmentioning
confidence: 99%
“…62.5 mcg/mL fucoidan was able to prevent shape change in the LPS exposed microglial cultures, and 125 mcg/mL inhibited NO production. In 2004 Li demonstrated the characteristic fragmented DNA (fDNA) observed in neuronal nuclei in Alzheimer brain was taken up by adjacent activated microglia which then became activated [93]. Blocking the scavenger receptors on the microglial cells with Fucus vesiculosis fucoidan at 40 ng/mL suppressed this uptake.…”
Section: Therapies From Fucoidanmentioning
confidence: 99%
“…Using various analytical methods (polymerase chain reaction (PCR), fluorescent in situ hybridisation (FISH), isotope and fluorescence labelling of pDNA with subsequent analysis), it is possible to detect DNA/DNA fragments in a wide array of mammalian cell types, such as: cytotoxic T cells [194], B cells [194,195], macrophages [171,194,196], other leukocytes [197], dendritic cells [196], Kupffer cells [170], liver scavenger endothelial cells [170], hepatocytes [198], keratinocytes [199], myocytes [156,159] and microglia cells [200]. In fish, DNA has so far only been detected in rainbow trout myocytes [57], head kidney macrophages of Atlantic salmon [201] and Atlantic cod [183], and in scavenger endothelial cells of Atlantic cod heart [183] and Atlantic salmon kidney [182].…”
Section: Cells Taking Up Dnamentioning
confidence: 99%
“…Some of these receptors also mediate effective endocytosis of soluble ligands. Earlier reports demonstrated that soluble ligands like pDNA or fragmented DNA, are taken up by cultured macrophages [230], microglia cells [200] and Kupffer cells [170] via a specific mechanism resembling scavenger receptors. However, scavenger receptor class A, that recognise a wide variety of anionic macromolecules is not responsible for pDNA uptake [171].…”
Section: Macrophagesmentioning
confidence: 99%
“…When activated, these receptors signal pathways associated with oxidative stress and inflammation. Scavenger receptors are a family of pattern recognition receptors (PRR) that are sensitive to repeating or ordered patterns of charge like those found on the SPM (Savill et al 1989;Grewal et al 1997;Yamasaki et al 2003;Li et al 2004). Toll-like receptors and the Mac-1 receptor are found on microglia and have PRR that when activated by xenobiotics, signal oxidative stress and inflammatory pathways (Jung et al 2005;Pei et al 2007).…”
Section: Discussionmentioning
confidence: 99%